Sistem Keamanan Jaringan Komputer Bridge Firewall Menggunakan Router Board Mikrotik Rb750 - Ahmad Robbahul Barra; Arif Rahman Sujatmika; Izzatul Umami (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Currently to get a strong firewall is still constrained by expensive costs. Only large companies or agencies can obtain these devices, while small and medium-sized companies are still unable to obtain reliable firewall devices. Therefore, it is necessary to need inexpensive security devices or firewalls for medium and small companies and agencies to protect computer networks from outside interference. Mikrotik RB 750 is a router that can be used to make a network security system that is reliable, inexpensive and easy to configure. In this study, the author tries to provide a network security system solution using Packet Filter Firewall with the router in bridge mode and compares network security systems in other research journals. From the results of the comparison, several series of network security protections are produced, namely changing the proxy to bridge mode, IP address protection, content protection with mangle, Mikrotik device protection, traceroute protection, port scanner protection, Bogon IP protection, and Bruteforce FTP protection. After conducting a series of tests from the results of the network protection setup using the Mikrotik RB 750 in bridge mode, the authors conclude that not all packets that pass through the bridge firewall device can be filtered. One of them is ICMP flooding packets. Mikrotik devices with Firewall bridge mode cannot calculate the number of ICMP packets that pass, so the author blocks ICMP packets with the 8:0 option (echo request) that goes to the local network.